Trimethoprim-sulfamethoxazole induced acute interstitial nephritis in renal allografts; clinical course and outcome. - Garvey,JP; Brown,CM; Chotirmall,SH; Dorman,AM; Conlon,PJ; Walshe,JJ (Clin Nephrol, 2009)
BACKGROUND: Acute interstitial nephritis (AIN) secondary to trimethoprim-sulfamethoxazole (TMP-SMX) is well documented as a cause of acute renal failure in native kidneys. TMP-SMX is the standard prophylactic agent against pneumocystis carinii (PCP) used in the early post-transplant period, however, it has to date only been indirectly associated with AIN in renal allografts. DESIGN, SETTING, PARTICIPANTS AND MEASUREMENTS: We describe eleven renal transplant patients with acute allograft dysfunction in whom a transplant biopsy demonstrated primary histopathologic features of allergic AIN, all of whom were receiving TMP-SMX in addition to other medications known to cause AIN. RESULTS: All cases occurred within 1 month of transplantation and accounted for 2.12% (11/518) of the total number of transplant biopsies performed during the study period. However, this figure increased to 10.1% (11/109) when those biopsies performed for early allograft dysfunction (< 1 month) were taken into account. After discontinuation of TMP- SMX alone, all patients had an immediate improvement in serum creatinine with excellent long term allograft function - mean improvement of serum creatinine from 465 micromol/l to 136 micromol/l at last follow-up (range 15 - 55 months). CONCLUSIONS: AIN secondary to TMP-SMX, although an uncommon cause of allograft dysfunction over the study period, accounted for over 10% of cases of allograft dysfunction within the first month of transplantation. Therefore, a high degree of clinical suspicion for TMP-SMX-induced AIN is warranted when confronted with early acute allograft dysfunction.